LIFELONG LEARNING QUALIFICATIONS IN THE CAREER JOURNEY OF THE DIGITAL TRANSFORMATION AGE (Third Sector Social Economic Review, 2021)
Globalization and developments in information and communication technologies have brought along many industrial, social and economic changes. The knowledge and skills that businesses expect from employees in the era of digital transformation have also changed. The concept of lifelong learning is a concept that expresses the continuous development of individuals in fields such as communication, science, technology, learning to learn, social citizenship and cultural awareness, and it has been included in many government packages around the world today. Based on the importance of this subject, in this research, it is aimed to determine the level of lifelong learning qualifications of vocational school students who meet the qualified personnel needs of the business world. In the research conducted for this purpose (n=341); The lifelong learning competencies of the participants in the research were determined at a high level, and their communication competency in a foreign language was determined at a medium level. According to the variables of gender, class, age and income status, the participants' perceptions of lifelong learning proficiency do not differ. It has been determined that having work experience and the education program cause a difference in lifelong learning qualifications and this difference is significant.
Keywords: Lifelong learning; Career; Digital transformation; Industry 4.0